Design and fabrication of table top sanding machine / Ahmad Daniel Haqal Zahid - Zahid, Ahmad Daniel Haqal (2023)
In carpeting activities such as shaping and finishing wood and other materials , we need to use a machine to speed up the work. The name of the machine is belt sander machine. But to do shaping and finishing wood and other materials for tools that are not large we can use a smaller belt sander machine. This is because the price of a belt sander machine in the market is quite expensive and not affordable with small work to be done. So a smaller belt sander machine that is much cheaper than the market price are very relevance. A little addition by adding other disc sander machine by using the same motor with the belt sander machine and to turn two processes into one machine. The expectation is that the final product accomplishes the goal to be affordable and small with the reasonable speed rate to the requirements